2014
DOI: 10.1186/1550-2783-11-18
|View full text |Cite
|
Sign up to set email alerts
|

The effect of almond consumption on elements of endurance exercise performance in trained athletes

Abstract: BackgroundAlmonds are a healthy tree nut food with high nutrient density. Their consumption has been shown to ameliorate oxidative stress, inflammation, etc. The objective of the study was to examine the effect of almonds on elements of endurance exercise performance in trained athletes.MethodsA 10-week crossover, placebo controlled study was conducted. Eight trained male cyclists and two triathletes were randomly assigned to consume 75 g/d whole almonds (ALM) or isocaloric cookies (COK) with equal subject num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Nut consumption by athletes is important, due to their high energy density and contents of monounsaturated fats, proteins (rich in tryptophan, leucine, and histidine), vitamins, minerals, insoluble dietary fiber, phytosterols, antioxidants and phenolic compounds (González, 2008;Yi et al, 2014). Therefore, the almost daily consumption of nuts by the international squash players participating in the present study is adequate.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nut consumption by athletes is important, due to their high energy density and contents of monounsaturated fats, proteins (rich in tryptophan, leucine, and histidine), vitamins, minerals, insoluble dietary fiber, phytosterols, antioxidants and phenolic compounds (González, 2008;Yi et al, 2014). Therefore, the almost daily consumption of nuts by the international squash players participating in the present study is adequate.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the almost daily consumption of nuts by the international squash players participating in the present study is adequate. It has been reported that the intake of this group of foods yields improvements in the endurance of athletes due to its contribution to the reserves and utilization of CH through improvement in glucose transport to the synthesis of skeletal muscle and glycogen, which enhances sports performance and reduces biomarkers of oxidative stress and inflammation (Yi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Yi et al 24 showed, in a study of Chinese cyclists, that the consumption of a food source a-tocopherol, the most common form of vitamin E present in nature, increased performance, time, distance, and endurance of these athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, athletes who supplemented with almonds exercised longer than those supplemented with isocaloric cookies, despite the lower carbohydrate content of the almonds [16]. Given the rising popularity of the Paleo diet, which favors high protein intake and lower carbohydrate intake, this food-based study is particularly timely.…”
Section: Diet Days To Weeks Prior (Adaptive Phase)mentioning
confidence: 99%
“…In contrast to the studies of macronutrients above, Yi et al employed a randomized cross-over design to compare a 4 week intervention of 75 grams of almonds per day compared to isoenergetic cookies on distance covered in a 20 minute cycling time trial [16]. They found the almond group was able to ride further than the cookie group (21.9 vs 20.2 km).…”
Section: Food Based Interventionsmentioning
confidence: 99%